2016
DOI: 10.1016/j.surfcoat.2016.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Innovating pulsed electrophoretic deposition of boehmite nanoparticles dispersed in an aqueous solution, into a model porous anodic film, prepared on aluminium alloy 1050

Abstract: International audienceThe present study investigates the pulsed electrophoretic deposition of boehmite particles, previously dispersed in an aqueous solution, into the pores of a model anodic film, prepared using phosphoric acid electrolyte, on an aluminium alloy 1050 (AA1050) substrate. Particles were successfully inserted into the pores, despite some limitations resulting both from the barrier layer, which transpired to be semi-conducting, and from water electrolysis. To address this issue, a pulsed electric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Accordingly, using them as aqueous solvents for suspension preparation in EPD has a limitation. 8-10 Therefore, non-aqueous mediums can be used to serve as the suspensions in EPD. 11 Besra and Liu 12 reported that the stability of particles in the suspension has a great influence on the quality of the coatings.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, using them as aqueous solvents for suspension preparation in EPD has a limitation. 8-10 Therefore, non-aqueous mediums can be used to serve as the suspensions in EPD. 11 Besra and Liu 12 reported that the stability of particles in the suspension has a great influence on the quality of the coatings.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is quite necessary to take effective measures to improve the corrosion resistance of alloys in a corrosive environment. 14 Traditionally, the anticorrosion strategies of Al alloys mainly consist of anodic oxidation, 15,16 chemical transformation 17 and organic coating, 18 etc. Although the protection efficiency is signicantly improved by these methods, the preparation processes are tedious and harmful to the environment.…”
Section: Introductionmentioning
confidence: 99%
“…This assumption seems reasonable, keeping in mind the multitude of intermetallic phases present in the alloy's composition [48,53,54]. The nucleation of local corrosion under the defects of the combined coating is strongly suppressed by the boehmite, formed during the treatment in boiling water, as proposed by Caubert et al [55]. Besides, supplemental suppression of the localized corrosion appears due to the formation of Keggin type (Al 13 O 4 (OH) 24 (H 2 O) 12 ) 7+ , (AlO 4 Al 12 (OH) 24 (H2O) 12 ) 7+ polyhydroxychlorides during the extended exposure to the 5 % NaCl model corrosive medium, as proposed in previous works [56,57].…”
Section: Groupmentioning
confidence: 85%